answersLogoWhite

0

7x - 3y = 37

2x - y = 12

You can eliminate y by multiplying both sides of equation 2 by minus 3 and then add:

7x - 3y = 37

-6x + 3y = -36

x = 1

substitute x =1 into either equation and solve y

2(1) -y =12

-y = 10

y = -10

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
TaigaTaiga
Every great hero faces trials, and you—yes, YOU—are no exception!
Chat with Taiga
FranFran
I've made my fair share of mistakes, and if I can help you avoid a few, I'd sure like to try.
Chat with Fran

Add your answer:

Earn +20 pts
Q: How do you solve this equation 7x-3yequals37 and 2x-yequals12 using the Elimination Method?
Write your answer...
Submit
Still have questions?
magnify glass
imp